IMPLEMENTASI PROGRAM MARKET DAY UNTUK MENGAJARKAN PEMAHAMAN LITERASI KEUANGAN ANAK USIA DINI DI PAUD BUSTANUL ULUM TUMAPEL - U’baidah, Shofiatul; Habibah, Shuhatul; Junaidi, Mahbub (Jurnal Murid, 2024)
This research explores the implementation of the market day program to teach early childhood financial literacy at PAUD Bustanul Ulum Tumapel. The research approach used is qualitative with a field approach method, involving data collection techniques through observation, interviews and documentation. Data were analyzed using a data reduction process, data presentation, and drawing conclusions. The case study was conducted at PAUD Bustanul Ulum Tumapel, Gresik Regency. Interviews with school principals, parents. The results of the research show that market day can improve PAUD Bustanul Ulum Tumapel in financial literacy.